2015
DOI: 10.7763/joebm.2015.v3.206
|View full text |Cite
|
Sign up to set email alerts
|

Using Importance-Performance Analysis in Evaluating Taiwan Blog e-Service Quality

Abstract: Abstract-This study uses Importance-Performance Analysis (IPA) in evaluating Taiwan blog e-service quality. Base on Importance-Performance Analysis, if the interface is smooth, and it provides multiplicity and uploading functions belonged to quadrant 1, (keep up the good work), and the most important blogs' future functions is sharing resources between blogs associated with quadrant 1, (keep up the good work). Finally, the result of this study is expected to serve as a useful guideline for Internet service pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
0
17
0
4
Order By: Relevance
“…[Insert Table 3 here] As IPA is a graphical technique, the boundary lines to separate the grid into four quadrants of the IPA matrix were defined by the overall means of the 15 attributes, following Martilla and James (1997), Yavas and Shemwell (2001), Huang et al (2006), Deng et al (2008) and Lin et al (2009). For traditional IPA, the self-stated importance and performance means were used for plotting the IPA matrix.…”
Section: Results Generated By Applying the Four Different Ipa Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…[Insert Table 3 here] As IPA is a graphical technique, the boundary lines to separate the grid into four quadrants of the IPA matrix were defined by the overall means of the 15 attributes, following Martilla and James (1997), Yavas and Shemwell (2001), Huang et al (2006), Deng et al (2008) and Lin et al (2009). For traditional IPA, the self-stated importance and performance means were used for plotting the IPA matrix.…”
Section: Results Generated By Applying the Four Different Ipa Approachesmentioning
confidence: 99%
“…Deng et al (2008) hold the view that implicit importance, which is derived from performance perceptions and aims to incorporate the determinant variable of performance into importance, may compensate the shortcomings and reduce the errors arising from subjective judgment. Different measures are used to assess the implicit statistical importance, including standardized/unstandardized regression coefficients, partial correlation, bivariate correlation, composite ranking, integrated partial correlation analysis and natural logarithmic transformation (Bacon, 2003;Deng, Kuo, & Chen, 2008;Huang, Wu, & Hsu, 2006;Matzler, Sauerwein, & Heischmidt, 2003;Slack, 1994). Crompton and Duray (1985) and Matzler et al (2003) found that deriving implicit importance using different methods actually results in similar outcomes.…”
Section: Measurement Of Attribute Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Sam and Tahir (2009) [8] examined the quality of the website such as usability, design, quality of information, trust, risk perception and empathy have significant influence on the intentions of consumers in the purchase of air tickets. Importance-Performance Analysis (IPA) is a simple and useful technique for identifying those attributes of a productor service that are most in need of improvement or that are candidates for possible cost-saving conditions without significant detriment to overall quality (Huang et al, 2015) [9]. This method was introduced by Martilla and James (1977) [10] and has been able to demonstrate the ability to provide managerial services with valuable information for measuring both satisfaction and the efficient allocation of resources in accordance with the format.…”
Section: Webqualmentioning
confidence: 99%
“…Tonge and Moore [27] used IPA method and gap analysis in assessment of marine environmental protection management. Huang, Wu and Hsu [10] used IPA method to probe the national highways' the long-range passengers satisfaction of service quality attributes. Levenburg and Magal [16] used IPA method to establish e-commerce strategies and resource allocation.…”
Section: Introductionmentioning
confidence: 99%